The Wage Premium of Globalisation: Evidence from European Mergers and Acquisitions - Harald Oberhofer; Matthias Stöckl; Hannes Winner (Austrian Institute of Economic Research (WIFO), 2012)
We provide evidence on the impact of globalisation on labour market outcomes analysing pay differences between foreign-acquired and domestically-owned firms. For this purpose, we use firm level data from 16 European countries over the time period 1999 to 2006. Applying propensity score matching techniques we estimate positive wage premiums of cross-boarder merger and acquisitions, suggesting that foreign acquired firms exhibit higher short-run (post-acquisition) wages than their domestic counterparts. The observed wage disparities are most pronounced for low paying firms (with average wages below the median). Finally, we find systematic wage premiums in Western European countries, but not so in Eastern Europe.
Keywords: 330; Globalisation; mergers and acquisitions; wage effects; propensity score matching; Lohnstruktur; Globalisierung; Multinationales Unternehmen; Übernahme; Fusion; Unternehmen; Schätzung; Europa; Westeuropa; Osteuropa